1987
DOI: 10.1021/j100306a030
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical and spectroscopic characterization of thin films of titanyl phthalocyanine: comparisons with vanadyl phthalocyanine

Abstract: The photoelectrochemlcal properties of vacuum-deposited thin films of titanyl phthalocyanine (TiOPc) are described. Continuous films between 60 and 400 nm in thickness show behavior like that of a highly doped p-type semiconductor, with open-circuit photopotentials (K^) that vary linearly in magnitude with the formal potential of the contacting redox couple (up to 0.7 V). Comparison of photocurrent action spectra and transmission absorbance spectra showed that two distinct phases of TiOPc were deposited from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 0 publications
5
67
0
Order By: Relevance
“…Different dimeric structures are possible, with two PC macrocycle planes parallel and the Al-OH oriented in the same direction (head-to-tail) or in the opposite direction (head-to-head or tail-to-tail). Similar results were observed for trivalent metal Pc's (21,(33)(34)(35)(36). Thus, the X-ray structure determinations of single crystals of several vacuum-deposited thin film Pc's that have a trivalent or tetravalent metal at centre (e.g.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Different dimeric structures are possible, with two PC macrocycle planes parallel and the Al-OH oriented in the same direction (head-to-tail) or in the opposite direction (head-to-head or tail-to-tail). Similar results were observed for trivalent metal Pc's (21,(33)(34)(35)(36). Thus, the X-ray structure determinations of single crystals of several vacuum-deposited thin film Pc's that have a trivalent or tetravalent metal at centre (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…PcGaC1, PcAlCl, PcInC1, PcVO) have shown that they have the tendency to aggregate in the solid state in either a cofacial stack (head-to-tail) or in various interleaved slipped stacks (head-to-head or tail-to-tail). It was proposed that the slipped configuration, in which the two PC phases have more degree of movement than the a -or P-phases reported before for other Pc's (22,23), is responsible for the strongly red-shifted visible absorbance spectra (33)(34)(35)(36). Infrared spectroscopy has been used by a number of authors as an indicator of crystallographic phase for phthalocyanines (23,26,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Macrocyclic metal complexes of porphyrin analogue structures such as metal-containing tetraazaporphyrins, phthalocyanines, naphthalocyanines and their substituted derivatives function as active compounds in various processes driven by visible light: photoredox reactions and photo-oxidation in solution [1][2][3][4], activity in the photodynamic therapy of cancer [5][6][7][8][9], photoelectrochemical cells [10][11][12], photovoltaic cells [12][13][14][15] and electrophotographic applications [16]. These properties are influenced by the kind of substituents (electron donating or electron withdrawing) at the ligand and by the kind of metal ion (closed-shell, open-shell electron configuration) in the core of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…the green dark product that precipitated was filtered off, successively washed with water and hot methanol. UV-Vis max in DMF (680 nm): (9). Yield: 10%; Following a similar synthetic procedure, 1-benzyl-4-(3,4-dicyanophenoxy)-1H-1,2,3-triazole 7 (0.155 g, 0.492 mmol), urea (0.087 g, 1,450 mmol), zinc acetate (0,026 g, 0,121 mmol), and ammonium molybdate (0,012 g, 0.01 mmol) were suspended in nitrobenzene (2 mL) and heated at 160 ∘ C for 8 h. Yield: (10%) UV-Vis max in DMF (700 nm); …”
Section: Synthesis Of Zinc Tetrakis (Propyn-3-yloxy) Phthalocyanine (8)mentioning
confidence: 99%
“…These properties arise from their electronic delocalization and make these compounds applicable in different fields of materials science; they are particularly promising as building blocks in nanotechnology. Some of the potential uses for phthalocyanines include nonlinear optical materials [1], liquid crystals [2], Langmuir-Blodgett (LB) films [3], optical data storage (computer recordable DVDs) [4], as electrochromic substances [5], low dimensional metals [6], and gas sensors [7], as photosensitizers [8], in photoelectrochemical cells [9] and electrophotographic applications [10]. Substitution has a strong influence on the -electron conjugation of the macromolecule, since it makes salvation easier [11].…”
Section: Introductionmentioning
confidence: 99%